Public Attitudes to Sentencing in Canada: Exploring Recent Findings - Roberts, Julian V. (Canadian journal of criminology and criminal justice, 2007)
This article reports findings from two representative public-opinion surveys that explored Canadians' attitudes toward three important sentencing issues: the severity of sentencing; the purposes of sentencing; and mandatory sentences of imprisonment. As has been found by polls over the past 30 years, most Canadians believe that sentencing practices are too lenient. The same result emerged from a poll conducted in 2005: 74% of respondents held the view that sentencing is too lenient - a finding consistent with polls conducted throughout the 1980s. With respect to the purposes of sentencing, strongest public support emerged for the restorative sentencing objectives of promoting a sense of responsibility in the offender and securing reparation for the crime victim. There was less support for the more traditional purposes of deterrence and incapacitation. This finding represents a marked contrast to findings from the last survey that evaluated public reaction to sentencing purposes (in 1985). Slightly more than half the sample in 2005 expressed support for mandatory sentencing - a result consistent with opinion surveys from the United States and Australia. However, there was strong public support for mandatory sentencing legislation that also permits a limited degree of judicial discretion. The public appear aware of the dangers of an absolute mandatory sentence of imprisonment and support mandatory sentences in which courts may impose a lesser sentence where exceptional circumstances exist. The implications of these findings for sentencing policy in Canada are discussed. [ABSTRACT FROM AUTHOR]